The use of probiotics in nutrition and herd health management in large Hungarian dairy cattle farms - Várhidi, Zsóka; Máté, Marietta; Ózsvári, László (Frontiers in Veterinary Science, 2022)
In the European Union there is an increasing need for farm animal nutrition products whose positive effects can replace antibiotics that have been heavily used for decades. Thus, the use of probiotics started to increase in the past few years. In this study, a survey on the practical use of probiotics in Hungarian dairy cattle farms and the related experience of farm nutrition experts was conducted. In addition, we surveyed the state of the Hungarian probiotics production and distribution. After direct request via phone, nutrition experts responsible for farm feeding programmes in 23 large commercial dairy cattle farms and 8 managers in different feed distributor companies in Hungary filled out the relevant on-line questionnaires in 2018. The results show that 69.6% of the surveyed farms used probiotics, most often aiming at the optimization of rumen fermentation, protection against stressors and supplementation of medical treatments. The most common beneficial effects of probiotics were more effective calf raising, larger milk yield, more stable rumen fermentation and improved stress-resistance. None of the respondents experienced any negative effects. In Hungary, 5 out of 8 feed companies produce probiotic products for cattle and one distributes them. Company managers generally think that farm nutrition experts do not have the up-to-date knowledge on probiotics, that is why, these products are often not used in an effective way, and the experts’ knowledge should be increased. The own experiments of the distributor companies show that the probiotic products can improve feed digestibility, efficacy of calf raising and reproductive performance of cows. According to the expectations of distributors, the next generation of probiotic products will be microencapsulated, will contain multiple strains and species of bacteria and prebiotics, too. The goal in the product development is to create probiotics with better effectiveness at a reasonable price, having a complex impact and easier application on herd level. It can be concluded that aiming at reducing the use of antibiotics, probiotics could play a more significant role in dairy cattle farms as part of preventive herd health programs and more widely used supplements of disease treatments.